2019
DOI: 10.1161/circulationaha.118.038571
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Regulates Atherogenesis by Attenuating Low-Density Lipoprotein Transcytosis and Vascular Inflammation Independently of Endothelial Nitric Oxide Synthase Activation

Abstract: Background-Atherosclerosis is driven by synergistic interactions between pathological biomechanical, inflammatory and lipid metabolic factors. Our previous studies demonstrated that absence of caveolin-1 (Cav1)/caveolae in hyperlipidemic mice strongly inhibits atherosclerosis, which was attributed to activation of endothelial nitric oxide synthase (eNOS) and increased production of nitric oxide (NO), reduced inflammation and low-density lipoprotein (LDL) trafficking. However, the contribution of eNOS activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 48 publications
4
94
0
1
Order By: Relevance
“…They have crossed CAV1-/with eNOS-/-mice into a proatherogenic background and found that CAV1 controls proatherogenic responses of endothelial cells to disturbed blood flow, including lipid trafficking, extracellular matrix (ECM) remodeling, and inflammatory signaling in early-stage ath-erosclerotic lesions. CAV1 also promotes proatherogenic matrix deposition leading to endothelial cell activation in atheroprone regions of the aorta [128]. Hence, these data indicate that CAV1-based therapeutics should be further studied to alleviate the burden of diabetic complications.…”
Section: Role Of Caveolin-1 In Oxidative Stressmentioning
confidence: 81%
“…They have crossed CAV1-/with eNOS-/-mice into a proatherogenic background and found that CAV1 controls proatherogenic responses of endothelial cells to disturbed blood flow, including lipid trafficking, extracellular matrix (ECM) remodeling, and inflammatory signaling in early-stage ath-erosclerotic lesions. CAV1 also promotes proatherogenic matrix deposition leading to endothelial cell activation in atheroprone regions of the aorta [128]. Hence, these data indicate that CAV1-based therapeutics should be further studied to alleviate the burden of diabetic complications.…”
Section: Role Of Caveolin-1 In Oxidative Stressmentioning
confidence: 81%
“… 28 , 29 Our findings showed no significant difference in LDL level by Cav1 genotype, although preclinical studies have shown that Cav1 may be involved in the regulation of lipoprotein metabolism and transcytosis of LDL. 30 , 31 Future prospective randomized controlled studies are needed to assess the impact of Cav1 genotype on the effectiveness of statins in lowering LDL.…”
Section: Discussionmentioning
confidence: 99%
“…d-PDMP might exert both anti-inflammatory and anti-oxidative functions via decreased ERK activation. Since increased lipid-raft levels are associated with inflammation, we measured the expression of Caveolin-1, a raft-specific marker [7,25]. A reduction in Caveolin-1 protein was found in d-PDMP-treated aortas ( Figure 5L).…”
Section: Gonadal Fat-pad Mass In Myriocin-treated Apoe −/− Mice Was Smentioning
confidence: 99%